Upaya Perlawanan Perempuan Afghanistan dalam Menghadapi Ancaman Opresi/Kebijakan Opresif Taliban - Oriza Dian Lestari (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
The Taliban managed to retake the Afghan capital, Kabul, on August 15, 2021, after 20 years ago the Taliban took control of the city. Many people, ranging from civilians to foreigners, especially women, are deprived of their freedom by implementing the policies they make. Various actions carried out by women are regulated by the Taliban such as going to school, how to dress, and others. this causes women to fight against the Taliban in order to regain their rights that have been taken away. This study uses a qualitative method with a literature study approach. The purpose of this study was to see what kind of resistance efforts were carried out by women in regaining their rights that had been taken by the Taliban in Afghanistan. This study will explain the condition of women before and after the Taliban came to power, the oppressive actions of the Taliban against women, women's efforts to fight against the Taliban's power and the obstacles faced by women in fighting against the domination of the Taliban. In the end, the various efforts that women continued to make to fight against the domination of the Taliban were met with threats of violence and murder and these actions further cornered the efforts of women's resistance